Stereotactic Radiosurgery for Intracranial Breast Metastases: A Systematic Review and Meta-Analysis - Almeida, Neil D.; Kuo, Cathleen; Schrand, Tyler V.; Rupp, Julia; Madhugiri, Venkatesh S.; Goulenko, Victor; Shekher, Rohil; Shah, Chirag; Prasad, Dheerendra (Cancers, 2024)
Background/Objectives: To determine the impact of stereotactic radiosurgery on outcomes of metastatic breast cancer with intracranial metastases. Methods: We systematically searched the PubMed and EMBASE databases for studies published between 1 January 1990 and 1 August 2024. Primary research articles evaluating the outcomes of stereotactic radiosurgery on intracranial metastases from breast cancer were included. Adverse events were defined as leptomeningeal disease, radiation necrosis, seizure, and headache. The pooled estimate was calculated using the DerSimonian and Laird approach. Results: Sixteen studies encompassing 1228 patients met the inclusion criteria. Our analysis revealed a median survival duration of 13.1 ± 3.8 months and a pooled 1-year overall survival rate of 53.1% after SRS treatment. There was a 29% local recurrence rate at 1 year and a 35% overall distant recurrence rate. In addition, our analysis found a relatively low rate of acute adverse events at 15.5%. Conclusions: SRS demonstrates promising efficacy and safety in managing intracranial metastases from breast cancer, with a favorable toxicity profile.